Analisis Implementasi Program Penanggulangan Gizi Buruk Di Puskesmas Wilayah Kerja Dinas Kesehatan Kota Sorong Provinsi Papua Barat - Zaenab Ismail; Martha Irene Kartasurya; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2016)
The prevalence of under-five children with severe malnutrition in Sorong city West Papua in 2008, 2009 and 2010 consecutively was 3.59%, 1.1% and 1.9%. Implementation of a program could be influenced by many factors such as communication, resources, disposition and bureaucracy factors. The objective of this study was to know the implementation of severe malnutrition control program at primary healthcare centers (puskesmas) in the working area of Sorong city health office West Papua in 2010. This was a qualitative study with cross sectional approach. Data was collected through in-depth interview using interview guideline. There were 5 primary healthcare centers studied with program executors as main informants. Triangulation informants were family or parents of under-five children with severe malnutrition, head of puskesmas and head of nutrition section of Sorong city health office West Papua province. Results of the study showed implementation of the program had not run according to the standard of implementation from the Ministry of Health. It was caused by not optimal communication that was done by Sorong city health office through program socialization. The availability of resources such as human resource to implement the program was insufficient. Only those who had nutrition educational background implemented the program and other workers were not involved in the program. There was no nutrition care team in all puskesmas. Additionally, the majority of the workers had not received training yet. Management of program funding was not according to the unit cost. Facilities were inappropriate and there was still improper puskesmas. The executor workers were needed for implementing the program; unfortunately due to less transparency and socialization, commitment was also low. No authority or standard operating procedure (SOP) given by Sorong city health office to puskesmas. In addition there was no supervision to the nutrition program workers. It was concluded that the implementation of severe malnutrition control program in Puskesmas in the working area of Sorong city health office West Papua province was not optimal. It was suggested to Sorong city health office to improve socialization about severe malnutrition control program to all program executors including heads of puskesmas in the working area of Sorong city health office; to create nutrition care and training teams. Funding allocation should be given to the right target and facilities should be completed.   Supervision, monitoring and evaluation were done continuously.